Starburst evolution: free–free absorption in the radio spectra of luminous IRAS galaxies - Clemens, M. S.; Scaife, A.; Vega, O.; Bressan, A. (Monthly notices of the Royal Astronomical Society, 2010)
We describe radio observations at 244 and 610 MHz of a sample of 20 luminous and ultra-luminous IRAS galaxies. These are a subset of a sample of 31 objects that have well-measured radio spectra up to at least 23 GHz. The radio spectra of these objects below 1.4 GHz show a great variety of forms and are rarely a simple power-law extrapolation of the synchrotron spectra at higher frequencies. Most objects of this class have spectral turn-overs or bends in their radio spectra. We interpret these spectra in terms of free–free absorption in the starburst environment. Several objects show radio spectra with two components having free–free turn-overs at different frequencies (including Arp 220 and Arp 299), indicating that synchrotron emission originates from regions with very different emission measures. In these sources, using a simple model for the supernova rate, we estimate the time for which synchrotron emission is subject to strong free–free absorption by ionized gas and compare this to expected H ii region lifetimes. We find that the ionized gas lifetimes are an order of magnitude larger than the plausible lifetimes for individual H ii regions. We discuss the implications of this result and argue that those sources which have a significant radio component with strong free–free absorption are those in which the star formation rate is still increasing with time. We note that if ionization losses are important, the resulting curvature of the radio spectrum would much reduce the often observed deficit in fluxes above ∼10 GHz.